Developing Digital Comics to Enhance Landslide Disaster Literacy among Elementary School Students - Candra Dewi; Muh. Waskito Ardhi; Mohd. Hanafi bin Mohd Yasin; Candra Dewi; Muh. Waskito Ardhi; Mohd. Hanafi bin Mohd Yasin (Universitas Negeri Malang, 2026)
This study’s core research objective is to develop a digital comic themed on landslide disaster mitigation. The comic is targeted at fifth-grade primary school students in East Java, Indonesia, meets three preset criteria (learning validity, practicality, and effectiveness), and deeply integrates literacy related to landslide disaster risk reduction. This study adopts the research and development (R&D) method and advances all work in full compliance with the ADDIE five-phase research framework throughout the implementation process. Research data is collected through observation, interviews, questionnaires, and academic achievement tests. Core research tools include supporting instruments: expert validation forms, teacher-student response questionnaires, and pre-test and post-test assessment questions. All data processing is completed using descriptive quantitative analysis and N-Gain analysis. The final core outcomes show that the developed product received a score of 83% from media experts, 87% from teaching material experts, and 95% from frontline practitioners, which meets the requirements for high effectiveness. The 89% student response rate reaches the standard for high practicality. The average N-Gain value of 0.6 represents a moderate learning gain, which can improve students’ academic performance, while also cultivating their learning motivation, active participation, and early-stage disaster prevention awareness.